The Prevalence of Extended Spectrum Beta-Lactamase Genes SHV, TEM and CTX-M in Clinical Isolates of Proteus mirabilis - Khoshaba, Ramina (Iraqi Journal of Science, 2025)
This study investigates the antibiotic resistance patterns in Proteus mirabilis isolates, with a specific focus on the presence of Beta-Lactamase genes, including SHV, TEM, and CTX-M, which are known to contribute to the bacterium’s ability to cause various diseases. A total of 100 urine samples were collected from patients confirmed urinary tract infections (UTIs), and out of these, only 20 of those samples were positively identified as Proteus mirabilis using cultural characteristics, biochemical examinations, and the Vitek II system. Antibiotic susceptibility was tested for 27 antibiotics. Results showed that isolates exhibited multi-drug resistance ranging from 10 to 19 antibiotics, with 100% resistance to Ampicillin, Erythromycin, Clindamycin, Clarithromycin, Penicillin G, Cephalothin and Cefaclor. Additionally, the isolates revealed high resistance to the third generation Cephalosporines of, including Ceftriaxone (85%), Cefotaxime (75%), Ceftazidime (55%), and Cefoperazone (45%). Using the Double Disk Synergy Test (DDST), eight isolates were confirmed to produce ESβL. Conventional PCR was conducted with specific primers to detect four distinct ESβLs (TEM, SHV, CTX-M-8, and CTX-M-9). Results revealed that CTX-M-8 was found in all eight isolates with phenotypic evidence of ESβL production, indicating that they are the most prevalent type of ESβL. At the same time, those for CTX-M-9, TEM-type and SHV type were 87.5%, 62.5% and 12.5 % respectively. In conclusion, all the examined isolates were found to produce ESβLs, particularly the CTX-M-8 gene.